2019
DOI: 10.1136/jmedgenet-2018-105879
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect size of the 15Q11.2 BP1–BP2 deletion and its contribution to neurodevelopmental symptoms: recommendations for practice

Abstract: BackgroundThe 15q11.2 deletion is frequently identified in the neurodevelopmental clinic. Case–control studies have associated the 15q11.2 deletion with neurodevelopmental disorders, and clinical case series have attempted to delineate a microdeletion syndrome with considerable phenotypic variability. The literature on this deletion is extensive and confusing, which is a challenge for genetic counselling. The aim of this study was to estimate the effect size of the 15q11.2 deletion and quantify its contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 46 publications
(46 reference statements)
3
50
0
Order By: Relevance
“…We confirmed the association of the deletion with CVM (OR = 1.73 [95% CI 1.08-2.75]; p = 0.03) and, in broad agreement with recent findings from others [17], with neuropsychiatric disorders (OR = 1.84 [95% CI 1.23-2.75]; p = 0.0043), measures of cognitive function, academic achievement and fecundity. We confirmed the association of BP1-BP2 deletion with CVM, which has been observed in some but not all previous studies [25][26][27]36]. The first study linking BP1-BP2 deletions with non-syndromic CVM showed an odds ratio of 8.2 [95% CI 1.06-62.98]; the point estimate for the risk associated with the deletion was much less in this study, but still falling within the 95% confidence interval of the estimate from the first study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirmed the association of the deletion with CVM (OR = 1.73 [95% CI 1.08-2.75]; p = 0.03) and, in broad agreement with recent findings from others [17], with neuropsychiatric disorders (OR = 1.84 [95% CI 1.23-2.75]; p = 0.0043), measures of cognitive function, academic achievement and fecundity. We confirmed the association of BP1-BP2 deletion with CVM, which has been observed in some but not all previous studies [25][26][27]36]. The first study linking BP1-BP2 deletions with non-syndromic CVM showed an odds ratio of 8.2 [95% CI 1.06-62.98]; the point estimate for the risk associated with the deletion was much less in this study, but still falling within the 95% confidence interval of the estimate from the first study.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the classification of the deletion for the purposes of clinical genetics and genetic counselling, we tend to agree with Jønch et al that the deletion should be classified as "pathogenic, of mild effect size" [36]. The effect on CVM is not sufficient to justify genetic testing in children presenting with CVM as their primary diagnosis, and our conclusions regarding neuropsychiatric manifestations of the deletion are in agreement both with that previous study, and others in the UKB cohort [17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the CNVs in this region are inherited either maternally or paternally [3,11]. Deletions were reported in individuals with developmental delay, motor and speech impairments, schizophrenia, epilepsy, behavioral problems, attention deficit hyperactivity disorder (ADHD), obsessive-compulsive behavior, dysmorphism, malformations and an unusually happy expression [11][12][13][14][15][16][17]. Unaffected carriers were reported to have decreased cognitive abilities and general measures of functioning [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we compared carriers to thousands of controls, which provides a better estimate of the general population mean, and therefore a more reliable estimate of effect sizes (57). The deletion has been proposed as a pathogenic CNV of mild effect size (58), which is in line with the smaller effect sizes found in the UK Biobank data. In the Icelandic sample, carriers were compared to 19 NoCNV controls, which may have led to an overestimation of the CNV effect.…”
Section: Discussionmentioning
confidence: 75%